In vivo imaging of tagged mRNA in plant tissues using the bacterial transcriptional antiterminator BglG. (24th November 2020) - Peña, Eduardo J.; Robles Luna, Gabriel; Heinlein, Manfred
Summary: RNA transport and localization represent important post‐transcriptional mechanisms to determine the subcellular localization of protein synthesis. Plants have the capacity to transport messenger (m)RNA molecules beyond the cell boundaries through plasmodesmata and over long distances in the phloem. RNA viruses exploit these transport pathways to disseminate their infections and represent important model systems to investigate RNA transport in plants. Here, we present an in vivo plant RNA‐labeling system based on the Escherichia coli RNA‐binding protein BglG. Using the detection of RNA in mobile RNA particles formed by viral movement protein (MP) as a model, we demonstrate the efficiency and specificity of mRNA detection by the BglG system as compared with MS2 and λN systems. Our observations show that MP mRNA is specifically associated with MP in mobile MP particles but hardly with MP localized at plasmodesmata. MP mRNA is clearly absent from MP accumulating along microtubules. We show that the in vivo BglG labeling of the MP particles depends on the presence of the BglG‐binding stem–loop aptamers within the MP mRNA and that the aptamers enhance the coprecipitation of BglG by MP, thus demonstrating the presence of an MP: MP mRNA complex. The BglG system also allowed us to monitor the cell‐to‐cell transport of the MP mRNA, thus linking the observation of mobile MP mRNA granules with intercellular MP mRNA transport. Given its specificity demonstrated here, the BglG system may be widely applicable for studying mRNA transport and localization in plants. Significance Statement: Increasing evidence indicates the ability of plants to move RNA species between cells and tissues. Studies to understand the mechanisms by which RNA molecules are transported depend on suitable methods by which the fate of RNA molecules can be addressed in vivo . By adapting components of the bgl operon in Escherichia coli, we achieved unprecedented resolution in localizing the tobacco mosaic virus Movement Protein mRNA and tracking its cell‐to‐cell movement in vivo .